IoT-Based Barcode Scanning System Implementation Using ESP32 for Enhancing Warehouse Stock Opname Efficiency - Pratama, Surya Alamsyah Putera; Hidayat, Hidayat; Rahim, Wendy G E; Nugraha, M Anggy (International Journal of Research and Applied Technology (INJURATECH), 2025)
Efficient inventory management is the cornerstone of modern warehouse activities; however, traditional stock opname procedures, relying on manual documentation, have often faced extremely significant challenges related to data inaccuracies, delays in procedures, and high human error probabilities. This paper proposes an innovative technological solution through the development of an IoT-enabled barcode scanning system designed to enhance the efficiency of the stock opname process within the warehouse facility. The developed system employs ESP32 microcontroller technology integrated with GM67 barcode-scanning capability, forming an integrated platform that captures inventory data in real time over WiFi communication protocols directly connected to Firebase cloud-based database infrastructure. The research methodology approaches R&D methodology through practical implementation at Bengkel AHAAS's warehouse facility, which is located in Cinambo, Bandung City. The experimental test results indicated significantly improved performance, with a scanning accuracy of 95% under optimal conditions, an average response time of 2.3 seconds in transmitting data to the database, and a functional working distance of up to 15 cm. The system was found to reduce the processing time of stock opname by approximately 60%, as opposed to prior methods that had been performed entirely manually.